PERANCANGAN ALGORITMA ANGGI (AA) DENGAN MEMANFAATKAN DIFFIE-HELLMAN DAN RONALD RIVEST (RC4) UNTUK MEMBANGUN SISTEM KEAMANAN BERBASIS PORT KNOCKING - Suhendar, Anggi Sri Septiani; Sajati, Haruno; Astuti, Yenni (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2013)
In managing a server, an administrator takes a variety of ways for ensuring the safety and cosiness of the system. One type of threat that attack on the server is done on a port that is in an open state, thus making people who do not have access rights to perform port scanning to infiltrate into the server. One solution to cope with the attack on the port can be done by using port knocking. Port knocking is a method that can be applied to the server with the workings of such a code to unlock the safe. Port knocking is done by inserting a predetermined port sequenced to open a specific port. At the port sequenced delivery process takes an additional authentication likes keyport. Anggi algorithm (AA) is an algorithm that is built by combination o f Diffie-Hellman and RC4. The algorithm is used for encryption and descriptions a keyport from client side to the server side. In the process of sending a keyport to be modified by using the arithmetic calculation. Process of encryption and description keyport is done to prevent some attacks on the server by hackers with extracting such information after successfully breaking into a port. The results o f implementation AA algorithm on the process of port knocking can secure the delivery process o f keyport and improve the security o f server.